Go WILD, not WEIRD - Newson, M (Equinox Publishing, 2021)
Reliance on convenience samples for psychological experiments has led to the oversampling of Western, Educated, Industrialized, Rich, and Democratic (WEIRD) populations (Henrich et al., 2010). Our analysis of academic articles from six leading psychology journals revealed a significantly lower percentage of studies from European and English-speaking nations (92%), compared to a decade ago (95%), largely due to more studies from Asia (6%). Further analysis of four cognitive science of religion (CSR) journals showed how a more representative field is possible (67% from the Western & Other region), with proportionately more studies in Latin America (4%) and Africa (7%) than psychology (<1% each). Thanks to its interdisciplinary nature, CSR is in a good position to address ‘WEIRD’ problems and may be able to offer psychology methodological and epistemological tools that involve diversifying sample populations, increasing ecological validity, capturing the causes and consequences of cultural variation, and developing novel methodologies. Despite the challenges, we encourage more researchers to embrace the lessons offered by CSR’s history of global and interdisciplinary research. Where WEIRD identifies the populations we need to stop privileging, conducting work that is not just Worldwide, but also In Situ, Local, and Diverse (WILD) is what researchers themselves can aspire to. Just as nineteenth century ‘armchair anthropologists’ were replaced by generations of ethnographers who went out into the real world to study human variation, so modern day psychologists need to conduct experiments outside the lab with suitably heterogeneous populations.